2015
DOI: 10.1370/afm.1815
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Apnea and Risk of Panic Disorder

Abstract: PURPOSE Epidemiological studies have identified a trend in the development of depressive and anxiety disorders following a diagnosis of sleep apnea. The relationship between sleep apnea and subsequent panic disorder, however, remains unclear.METHODS Using a nationwide database, the Taiwan National Health Insurance Research Database, patients with sleep apnea and age-, sex-, income-, and urbanization-matched control patients who did not have sleep apnea were enrolled between 2000 and 2010. Patients with a prior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Many panic disorder (PD) patients experience respiratory symptoms, including hyperventilation, sleep apnea, chest pain, and dyspnea [1][2][3] . According to Klein's "False suffocation alarm hypothesis", excessive sensitivity to respiratory stimuli is at the core of PD 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Many panic disorder (PD) patients experience respiratory symptoms, including hyperventilation, sleep apnea, chest pain, and dyspnea [1][2][3] . According to Klein's "False suffocation alarm hypothesis", excessive sensitivity to respiratory stimuli is at the core of PD 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, they seemingly have a higher sensitivity to other respiratory stimuli, such as hypoxic challenge 21 , 22 and hyperventilation 23 . Finally, connections between sleep apnea and PD have been reported 24 . Overall, although the respiratory system of patients with PD is not so dysfunctional to induce a full-blown respiratory disease, it might be more unstable and sensitive than that of subjects without PD.…”
Section: Are Panic Attacks Really the Results Of False Alarms?mentioning
confidence: 98%
“…The method for enrolling study subjects is shown in Figure 1. Patients with SA diagnosis between March 1, 1995 and December 31, 2013 were identified by using the International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9-CM) codes of 780.51, 780.53, and 780.57, as validated in previous studies [13,15,16,17,18,19]. The dates of their first SA diagnosis were defined as their index dates.…”
Section: Methodsmentioning
confidence: 99%